Barriers to Local Government Legal Policy in Fulfilling Social Security for Vulnerable Workers - Fauzani, Muhammad Addi; Wahyuningsih, Aprillia; Rahman, Diva Febrina Nurcahyani (As-Siyasi: Journal of Constitutional Law, 2025)
This study examines, first, the barriers of the position of the Regional Government and the character of vulnerable workers in social security for vulnerable workers. Second, to formulate legal policies that can be taken by the Regional Government in providing social security for vulnerable workers. The study uses a normative legal method and a 2 (two) model approaches consisting of a statutory approach and a conceptual approach. The results of the study conclude, first, the position of the Regional Government in social security for vulnerable workers is still regulated abstractly and partially. However, in general, based on the analysis of several regulations above, the Regional Government has the authority to organize social security for vulnerable workers. The criteria for vulnerable workers are economically and socially vulnerable, vulnerable in terms of work risks and vulnerable to job loss. The Regional Government needs to provide social security for vulnerable workers because they have double vulnerabilities. Second, the regional legal policies that can be taken in providing social security for vulnerable workers are: a) harmonizing laws and regulations both vertically and horizontally; b) determining the form of the legal policy basis and the content of the material in providing social security for vulnerable workers; c) determining the criteria for vulnerable workers and participation in employment social security; d) measuring the amount of financing needed.